2021
DOI: 10.3389/fonc.2021.655630
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Clinical Implications of the Retinoblastoma (RB)-E2F Pathway in Gastric Cancer

Abstract: Gastric cancer is the most common malignant tumor in the digestive tract, with very high morbidity and mortality in developing countries. The pathogenesis of gastric cancer is a complex biological process mediated by abnormal regulation of proto-oncogenes and tumor suppressor genes. Although there have been some in-depth studies on gastric cancer at the molecular level, the specific mechanism has not been fully elucidated. RB family proteins (including RB, p130, and p107) are involved in cell cycle regulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 170 publications
0
16
0
1
Order By: Relevance
“…The E2F family is an important transcription factor family, which plays a regulatory role in cell cycle progression, DNA replication, DNA repair, cell differentiation, proliferation, and apoptosis. [11][12][13] Sun et al 17 analyzed the expression of E2F1 in patients with lung cancer and found that E2F1 mRNA and protein levels in lung squamous cell carcinoma and lung adenocarcinoma were higher than those in normal tissues. Wang et al 18 found that E2F1 can promote the epithelial-mesenchymal transformation of small cell lung cancer by regulating and participating in cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E2F family is an important transcription factor family, which plays a regulatory role in cell cycle progression, DNA replication, DNA repair, cell differentiation, proliferation, and apoptosis. [11][12][13] Sun et al 17 analyzed the expression of E2F1 in patients with lung cancer and found that E2F1 mRNA and protein levels in lung squamous cell carcinoma and lung adenocarcinoma were higher than those in normal tissues. Wang et al 18 found that E2F1 can promote the epithelial-mesenchymal transformation of small cell lung cancer by regulating and participating in cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle-related transcription factor E2F transcription factor 1 (E2F1) is the most important transcriptional activator of the Rb/E2F pathway, which regulates the progression from phase G 1 to phase S of the cell cycle. [11][12][13] E2F1 can participate in apoptosis induction in a p53dependent or independent manner. Yamazaki et al 14 found that high levels of E2F1 had shorter recurrence free survival and poor prognosis in patients with OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…As the first member discovered, E2F1 is a transcription co-factor that interacts with retinoblastoma protein (RB) to regulate the transcription of cell cycle-related proteins [ 6 ]. The cyclin dependent kinase 4 (CDK4)-pRB-E2F1 axis has been shown to be essential for cell cycle progression in normal and cancer cells, and high expression of E2F1 has been found to promote the proliferation of cancer cells by transactivating cell cycle-related kinases [ 7 , 8 ]. Moreover, because E2F1 is a critical transcription factor, it may also modulate cell cycle progression through its regulation of the transcription of other genes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The loss of function of RB enables unregulated cell cycle progression, thereby promoting tumor growth. RB is inactivated by genetic or functional inactivation in many human cancers, including retinoblastoma, small‐cell lung cancer, prostate cancer, breast cancer, and GC 14,16–18 …”
Section: Introductionmentioning
confidence: 99%